Does Including Momentum Factor Into Fama-French Five-Factor Model Predict Better Return In Indonesia? - Michael Diptana Setiawan Sutedja; Liliana Inggrit Wijaya (Syntax Literate, 2022)
The addition of momentum factor to the Fama-French Five-Factor Model in recent studies encourages investors to reconsider their investment strategies. The aim of this research is to compare the explanatory power of the Fama-French Five-Factor Model Plus Momentum (FF5F Plus Momentum) and the Fama-French Five-Factor Model (FF5F) to portfolio return of stocks listed in the Kompas100 Index over the 2010-2019 period. This research also aims to describe the relation and significance of each factor (market risk, size, book-to-market equity or value, profitability, investment, and momentum) in the FF5F Plus Momentum model to the excess return. This research uses the Ordinary Least Square method for multiple linear regression on 115 observations done to the 24 portfolios formed. The research finds that the market risk premium, size and book-to-market equity have positive and significant effects on return, profitability and investment have no significant effect on return and momentum has negative and significant effect on return. FF5F Plus Momentum model is found to have higher explanatory power than the FF5F model. This result suggests investors to consider the stocks in the Kompas100 Index that have small market capitalization, high book-to-market equity and small yearly return in the previous one-year period for their portfolio